Butterfly valves : torque, head loss, and cavitation analysis. (American Water Works Association, 2001)
Annotation Rather than specifying an AWWA standard, this manual presents engineers and technicians with a recommended method for calculations associated with the use and specification of butterfly valves in water systems. It includes the basics of butterfly valve design, definitions, and supporting examples, 27 figures, and a table. c. Book News Inc.
Keywords: Water-pipes -- Valves.; Butterfly valves.; elektronické knihy; electronic books